Pengukuran Efisiensi Organisasi Pengelola Zakat Dengan Metode Data Envelopment Analysis - Aulia Zahra; Prayogo P. Harto; Ahmad Bisyri ASH (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2016)
This study aims to determine the level of efficiency of Zakat Management Organization period 2012-2014 using Data Envelopment Analysis (DEA) method with the production approach. Data Envelopment Analysis (DEA) is a non-parametric method used to measure the efficiency level of Decision Making Units (DMU). This method measures the ratio between output and input which are compared between the studied Zakat Management Organization. Output variables used are fund collected and channeled fund. While input variables used are personnel costs, socialization costs, and other operational costs. The results of this study show that the efficiency of Zakat Management Organization in the year 2013 is still better than in 2012 and 2014, both technically (93,50%), scale (73,28%), and overall (70,54%). Calculation of 7 Zakat Management Organization in 2013 with the assumption of Constant Return to Scale (CRS), shows only 3 Zakat Management Organization efficient, that is YBM BRI, BSM Ummat, and BAMUIS BNI. The main cause of inefficiency from the output oriented measures is channeled fund and fund collected, which is equal 49,23% and 48,13%. While the input oriented measures states that the source of inefficiency is the personnel costs (33,42%), the socialization costs (33,72%), and the cost of other operational (32,29%).